2016
DOI: 10.1038/srep38224
|View full text |Cite|
|
Sign up to set email alerts
|

Microtubule stabilising peptides rescue tau phenotypes in-vivo

Abstract: The microtubule cytoskeleton is a highly dynamic, filamentous network underpinning cellular structure and function. In Alzheimer’s disease, the microtubule cytoskeleton is compromised, leading to neuronal dysfunction and eventually cell death. There are currently no disease-modifying therapies to slow down or halt disease progression. However, microtubule stabilisation is a promising therapeutic strategy that is being explored. We previously investigated the disease-modifying potential of a microtubule-stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Together, these studies implicate ADNP/NAP in synaptic plasticity, involving EB proteins (Jaworski et al, 2009 ; Oz et al, 2014 ). While these results explained the previously observed NAP interaction with microtubules, bringing into focus the SIP motif (Gozes et al, 2016 ; Quraishe et al, 2016 ) and suggesting an amplifier effect at the microtubule tip, the molecular mechanism of increased Tau hyperphosphorylation, as a consequence of ADNP deficiency and protection by NAP against tauopathy (Vulih-Shultzman et al, 2007 ; Matsuoka et al, 2008 ; Shiryaev et al, 2009 ; Jouroukhin et al, 2013 ), still required further investigations.…”
Section: The Identification Of the Nap/adnp Eb-direct Interaction Andsupporting
confidence: 77%
“…Together, these studies implicate ADNP/NAP in synaptic plasticity, involving EB proteins (Jaworski et al, 2009 ; Oz et al, 2014 ). While these results explained the previously observed NAP interaction with microtubules, bringing into focus the SIP motif (Gozes et al, 2016 ; Quraishe et al, 2016 ) and suggesting an amplifier effect at the microtubule tip, the molecular mechanism of increased Tau hyperphosphorylation, as a consequence of ADNP deficiency and protection by NAP against tauopathy (Vulih-Shultzman et al, 2007 ; Matsuoka et al, 2008 ; Shiryaev et al, 2009 ; Jouroukhin et al, 2013 ), still required further investigations.…”
Section: The Identification Of the Nap/adnp Eb-direct Interaction Andsupporting
confidence: 77%
“…The concept of utilizing MT-stabilizing agents to treat tauopathies has been discussed for some time [ 31 ], and our studies and those from others over the past several years have demonstrated the potential of this therapeutic strategy in tauopathy mouse models [ 24 27 , 32 , 61 , 62 ], as well as in other tau model systems [ 63 , 64 ]. Among traditional small molecule MT-stabilizing compounds, both EpoD and the abeotaxane, TPI-287, have progressed to Phase 1b clinical testing, where each was examined in short 2–3 month studies in AD and/or tauopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…MT stabilizing peptides are another option chosen to restore MT stability (Quraishe et al, 2016; Mondal et al, 2018). A peptide such as the PS3 octapeptide was designed from the taxol-binding pocket of β-tubulin (Mondal et al, 2018).…”
Section: Perspectivesmentioning
confidence: 99%